Enhancing cane and sugar productivity applying variable modes of plant growth regulators in sugarcane (Saccharum sp. complex) cultivation under coastal climatic conditions of India - PATNAIK, J R; NAYAK, P K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was carried out for three crop seasons at Sugarcane Research Station, Nayagarh (Odisha) during spring seasons of 2015-16, 2016-17 and 2017-18 to assess the effect of ethrel and gibberellic acid on growth, yield attributing characters, yield and quality of sugarcane (Saccharum sp. complex). Pooled data of three years study indicated that different treatments with plant growth regulators had significant effect on growth, yield and quality parameters of sugarcane. Germination percent of cane buds was the highest in the treatment involving planting of sugarcane setts after overnight soaking in 100 ppm ethrel solution followed by foliar application of gibberellic acid @35 ppm at 90,120 and 150 days after planting (DAP). Other sugarcane growth parameters, viz. number of tillers and plant heights were significantly higher with the application of growth regulators which produced higher number of millable canes (at harvest) than that of other treatments in the test. Overnight soaking of cane setts in 100 ppm ethrel solution followed by foliar application of gibberellic acid @35 ppm at 90,120 and 150 days after planting also produced significantly higher yield parameters, viz. number of millable cane (84.26’ 000 ha-1), cane length (313.6 cm), cane girth (2.94 cm) and single cane weight (1.64 kg) as compared to conventionally planted sugarcane crop. There was no significant influence on juice quality parameters due to various treatments in this study. However, overnight soaking of setts with 100 ppm ethrel solution followed by foliar application of gibberellic acid @ 35 ppm at 90, 120 and 150 days after planting showed comparatively higher values in all the juice quality parameters. Significantly higher cane and sugar yields of 116.14 t/ha and 12.82 t/ha, respectively were obtained with planting of sugarcane after overnight soaking in 100 ppm ethrel solution followed by gibberellic acid spray @ 35 ppm at 90, 120 and 150 days after planting. The above higher yields were attributed mainly to marked improvement in growth and yield attributes in response to application of plant growth regulators. Therefore, it can be concluded that combined application of ethrel and gibberellic acid had the positive effect to improve the growth parameters, yield and quality of sugarcane.